Existential-humanistic therapy - Bugental, James F. T.; Bugental, James (Needham Heights, MA : Allyn & Bacon Professional)
The approach in this video is generally considered a life-changing therapy and is based on the belief that who we are, what we do, and what we value is ours to choose
Moderator: Jon Carlson, Diane Kjos
Keywords: Psychotherapy; Counseling